Evaluation of the Engineering Curriculum Elements for Compliance - A. I. Chuchalin (Высшее образование в России)
Rubrics have been developed to evaluate the level of compliance of curriculum elements with the recommendations of the CDIO-FCDI-FFCD Standards in the process of modernizing engineering programs for undergraduate, graduate and postgraduate studies. As an example, the author presents the results of the evaluation of engineering undergraduate program courses for compliance with the recommendations of the CDIO Standards in the form of total and differentiated ratings of the modules of the humanities and social sciences, natural sciences and mathematics, basic engineering and specialized professional courses. Based on the ratings, the initial (before modernization) and planned (after modernization) levels of compliance of the program modules with the recommendations of each of the 12 CDIO Standards are determined. Using the rubrics enables to involve all the instructors in the process of engineering program modernization.